Pneumococcal problem in Turkey [Türkiye'de pnömokok problemi] - (:unkn) unknown (My University, 2010)
Epidemiologic data related to pneumococcal diseases are very limited in Turkey, despite the fact that pneumococcus is the most important organism causing childhood bacterial diseases such as pneumonia, meningitis, sepsis, acute otitis media, and an important cause of mortality and economic burden. Therefore, projections of some published local surveillance data as well as national disease burden data need to be projected and assumptions used in order to obtain information on the national pneumococcal disease burden. Such an analysis reveals that approximately 2,000 children under 5 years of age die, mostly because of pneumococcal pneumonia, 114,000 life years were lost and 110 million US Dollars spent for treatment of pneumococcal diseases in Turkey.
Keywords: Disease burden; Pneumococcus; Turkey